La acción tutorial en los estudiantes universitarios con discapacidad - Gairín Sallán, Joaquín; Muñoz Moreno, José Luís (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
This article places an emphasis on the importance of tutorials for students with a disability in universities. It presented the most significant results of the study of tutorials carried out in help services, units or offices for students with a disability inmore than 45 Spanish universities, in relation to promotion, reception, completion and graduation. The contributions highlight the importance of organising a response through a Tutorial Action Plan made up of the stages of motivation and awareness-raisin, planning, execution, evaluation and institutionalisation. Among the principle conclusions, the importance of moving towards a truly inclusive university through tutorial activity is highlighted, thereby providing a guide for providing assistance to university students with a disability.

Este aporte pone énfasis en la importancia de la acción tutorial dirigida al colectivo de estudiantes con discapacidad en el contexto universitario. Presenta los resultados más significativos del estudio que sobre actuaciones tutoriales realizan los Servicios, Unidades u Oficinas de atención a los estudiantes universitarios con discapacidad de más 45 universidades españolas, en relación con la promoción, la acogida, la permanencia y el egreso. Los aportes remarcan la importancia de organizar la respuesta a través de un Plan de Acción Tutorial orquestado desde las etapas de motivación y sensibilización, planificación, ejecución, evaluación e institucionalización. Entre las principales conclusiones, sobresale la importancia de avanzar hacia una universidad realmente inclusiva desde la acción tutorial, proporcionando, al respecto, una Guía para la atención a los alumnos universitarios con discapacidad.
Tutorials in university students with a disability
Keywords: Tutoría; Universidades; Discapacidad; Estudiantes Impedidos; Tutorial; Universities; Disability; Disabled Students; https://purl.org/pe-repo/ocde/ford#5.03.00